Challenges Of The Indirect Management Of Eu Funds In Albania - Totozani, Neritan (European Scientific Journal, ESJ, 2016)
Instrument of Pre-Accession programme assistance of European Union applies since 2007 in the Western Balkan countries and aims at preparing successfully the relevant countries for future EU integration. Albania benefits from IPA funds which plays a key role in the development of the administrative capacities of the Western Balkans countries. By strengthening the administrative capacities of these countries, IPA will enable them to take over the funds, the program management and ultimately the overall integration process. Preparing to profit from and ultimately manage IPA funds allows beneficiaries countries, for future efficient management of the so-called Structural and Cohesion Funds that Member States receive to better integrate their poorer regions and infrastructure. This study aims at identifying the value and complexity of such process concluding with the efforts and challenges in the near future toward being a fully fledged member of European Union. It is of great importance the way how Albania absorbs these funds. In this regard, i will assess the process of indirect management of IPA funds in Albania taking into consideration their actual status. In conclusion, this study is very important for the fact it gives a consolidated assessment of the challenges, needs and relative importance of transferring all management aspects of European Union financial assistance to the beneficiaries countries which will further strengthen the complementarily of the accession process and overall national development policies. Also, it will provide recommendation for strengthening administrative capacity and preparing national and local structures and authorities to plan and implement such programmes remain major challenges which the enlargement countries need to address rigorously from an early stage of the process.